2016
DOI: 10.1111/imj.12979
|View full text |Cite
|
Sign up to set email alerts
|

Baseline abnormal liver function tests are more important than age in the development of isoniazid‐induced hepatoxicity for patients receiving preventive therapy for latent tuberculosis infection

Abstract: The completion rate of 77% and rate of INH-induced hepatic dysfunction of 3% is comparable with the literature. We found no age association with the risk of INH-induced hepatic dysfunction; however, there was a significant and linear association with the degree of liver function abnormality during INH therapy and the presence of abnormal baseline LFT. Routine LFT monitoring allowed early cessation of INH in those with significant but asymptomatic hepatitis who did not meet criteria for ATS/CDC LFT monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…In a systematic review of age-related risk of hepatotoxicity by treating LTBI in 2010, the overall rates of hepatotoxicity were low; associated hospitalisation or mortality was extremely uncommon [46]. The use of IPT was concluded as safe in older patients with close clinical or biochemical monitoring and education [46], which had also been documented by recent studies [45, 47]. …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a systematic review of age-related risk of hepatotoxicity by treating LTBI in 2010, the overall rates of hepatotoxicity were low; associated hospitalisation or mortality was extremely uncommon [46]. The use of IPT was concluded as safe in older patients with close clinical or biochemical monitoring and education [46], which had also been documented by recent studies [45, 47]. …”
Section: Discussionmentioning
confidence: 95%
“…However, in most cases of serious toxicity, the patient either was not monitored for clinical or biochemical toxicity, continued to take the drug without specific guidance, or had complicating underlying liver disease or alcohol abuse. Abnormal liver function was found with more impacts than age on the development of isoniazid-induced hepatotoxicity [45]. In a systematic review of age-related risk of hepatotoxicity by treating LTBI in 2010, the overall rates of hepatotoxicity were low; associated hospitalisation or mortality was extremely uncommon [46].…”
Section: Discussionmentioning
confidence: 99%
“…29 There was also a similar prevalence of grade 2 and 3 liver toxicity events compared to the 6 month open label phase of the BOTUSA study. 30 …”
Section: Discussionmentioning
confidence: 66%
“…Among them, the risk of hepatotoxicity and mortality in the elderly is mainly concerned. However, recent studies demonstrated abnormal liver function absent of monitoring and quick response had more impacts than age on the development of isoniazid-induced hepatotoxicity [ 50 , 73 ]. In a systematic review of the age-related risk of hepatotoxicity by treating LTBI, the overall rates of hepatotoxicity were low; associated hospitalization or mortality was extremely uncommon [ 50 ].…”
Section: Discussionmentioning
confidence: 99%